2020
DOI: 10.1021/acs.jpclett.0c03153
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Biexciton Binding in Perovskite Semiconductor Nanocrystals Measured with Two-Dimensional Spectroscopy

Abstract: Perovskite semiconductor nanocrystals have emerged as an excellent family of materials for optoelectronic applications, where biexciton interaction is essential for optical gain generation and quantum light emission. However, the strength of biexciton interaction remains highly controversial due to the entangled spectral features of the exciton- and biexciton-related transitions in conventional measurement approaches. Here, we tackle the limitation by using polarization-dependent two-dimensional electronic spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 70 publications
10
37
2
Order By: Relevance
“…A possible explanation for this broadening is the presence of multiple decay routes from the BX to the 1X state, possibly through thermally excited hot BX states which are close energetically to the lowest BX state. 31 , 34 We note that this is qualitatively different from observations in core/shell/shell CdSe/CdS/ZnS NCs. 16 , 17 However, II-VI semiconductor NCs feature more pronounced spectral diffusion compared to LHP NCs.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…A possible explanation for this broadening is the presence of multiple decay routes from the BX to the 1X state, possibly through thermally excited hot BX states which are close energetically to the lowest BX state. 31 , 34 We note that this is qualitatively different from observations in core/shell/shell CdSe/CdS/ZnS NCs. 16 , 17 However, II-VI semiconductor NCs feature more pronounced spectral diffusion compared to LHP NCs.…”
Section: Discussioncontrasting
confidence: 89%
“… 30 Similar trends have been demonstrated for CsPbBr 3 at cryogenic temperatures using two-dimensional electron spectroscopy. 31 In addition, analyses of TA measurements by Ashner et al , that do not employ short-delay spectra, did not result in large positive values (but rather in small negative values of a few meV). 14 Together, these observations suggest that ε b measured when both excitons are at the band edge would be lower than that measured when the first exciton is still hot.…”
Section: Discussionmentioning
confidence: 93%
“…Biexciton resonances in PNCs thus manifest in one-quantum spectra, specifically as negative peaks in the real-quadrature component [62]. This was observed in a recent study by Huang et al which applied MDCS to CsPbBr 3 PNCs in order to extract the biexciton binding energy as a function of nanocrystal size and temperature [61]. As shown in the real-quadrature one-quantum spectrum plotted in figure 7(a), a negative peak is observed that is red-shifted along the emission energy axis (relative to the positive single-exciton peak located at |ℏω τ | = |ℏω t |) by a value identical to the biexciton binding energy.…”
Section: Higher-order Exciton Complexesmentioning
confidence: 77%
“…30 Similar trends have been demonstrated for CsPbBr 3 at cryogenic temperatures using two dimensional electron spectroscopy. 31 In addition, analyses of TA measurements by Ashner et al, that do not employ short-delay spectra, did not result in large positive values (but rather in small negative values of few meV). 16 Together, these observations suggest that ε b measured when both excitons are at the band edge would be lower than that measured when the first exciton is still hot.…”
Section: X Emission Peak (Ev)mentioning
confidence: 93%